One Year Outcomes and Stability of a Novel Scleral Anchored Intraocular Lens - Edoardo Abed; Matteo Forlini; Edlira Bendo; Aurelio Imburgia; Alessandro Mularoni; Corrado Gizzi; Giuseppe Santino; Daniele Corazza; Giacomo Costa (Journal of Ophthalmology)
Purpose. To assess one year results and stability of the implantation of a scleral anchored intraocular lens (IOL). Design. Interventional prospective case series. Methods. Sixty eyes of 60 patients affected by either aphakia or IOL dislocation were included in this study. Patients underwent vitrectomy, scleral fixation of the IOL, and, if present, dislocated IOL removal. Patients were evaluated preoperatively and at 1, 3, 6, and 12 months after surgery by best-corrected distance visual acuity (BCVA) assessment, intraocular pressure (IOP) measurement, corneal specular microscopy, and optical coherence tomography (OCT) of both the macula and anterior segment. Results. At twelve months, mean BCVA significantly improved (p<0.0001), and none of the patients experienced a decrease of visual acuity. A 10% decrease of endothelial cell count occurred after surgery. Cystoid macular edema occurred in three patients (5%). A transient increase of intraocular pressure was noted in 7 cases (12%). At one month, horizontal and vertical IOL tilt was 1.04 ± 0.87 and 0.74 ± 0.71 degrees, respectively, and did not significantly change in the follow-up (p>0.05). None of the patients had decentration or dislocation of scleral-fixated IOL during the follow-up. Conclusion. Implantations of scleral plug fixated IOL provide good visual results, low complication rate, and excellent stability of the lens until one-year follow-up.